Prediction of Thermal Distribution in an Internally Heated Radiative-Convective Moving Porous Fin with variable Thermal Conductivity using Homotopy Perturbation Method - Suraju Aremu Oladosu; Rafiu Olalekan Kuku; Gbeminiyi Musibau Sobamowo; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
Thermal distribution of a rectangular moving convective-radiative porous fin with temperature-dependent thermal conductivity and internal heat generation is analyzed in this work homotopy perturbation method. With the aid of the analytical solutions, the impacts of the model parameters on the thermal behaviour of the fin are investigated.  The parametric analysis reveals that increase in porosity and convective parameters, the rate of heat transfer from the fin increases and consequently improves the efficiency of the fin. The values of the temperature distribution in the fin increase as the Peclet number increases. However, as thermal conductivity and internal heat generation increase, the rate of heat transfer from the fin decreases. Therefore, the operational parameters of the fin must be carefully selected to ensure that the fin retains its primary purpose of removing heat from the primary surface.